Dielectric Elastomers UV-Cured from Poly(dimethylsiloxane) Solution in Vinyl Acetate - Park, Seung Koo (Polymers (Basel), 2020)
Poly(dimethylsiloxane) (PDMS) has been extensively used as an electroactive polymer material because it exhibits not only excellent moldability but also mechanical properties sufficient enough for electroactive performance despite low dielectric permittivity. Its low dielectric property is due to its molecular non-polarity. Here, we introduce a polar group into a PDMS elastomer by using vinyl acetate (VAc) as a crosslinker to improve the dielectric permittivity. We synthesized a high-molecular weight PDMS copolymer containing vinyl groups, namely poly(dimethylsiloxane-co-methylvinylsiloxane) (VPDMS), and prepared several of the VPDMS solutions in VAc. We obtained transparent PDMS films by UV curing of the solution layers. Electromechanical actuation-related physical properties of one of the UV-cured films were almost equivalent to or superior to those of platinum-catalyzed hydrosilylation-cured PDMS films. In addition, saponification of the UV-cured film significantly improved the electrical and mechanical properties (ɛ′ ~ 44.1 pF/m at 10 kHz, E ~ 350 kPa, ɛ ~ 320%). The chemical introduction of VAc into PDMS main chains followed by saponification would offer an efficacious method of enhancing the electroactive properties of PDMS elastomers.